2023
DOI: 10.1039/d3ob00296a
|View full text |Cite
|
Sign up to set email alerts
|

Cu(ii)-catalyzed domino construction of spironaphthalenones by dearomatization of β-naphthols and using N,N-dimethylaminoethanol as a C1 synthon

Abstract: Herein, a Cu(II)-catalyzed facile construction of synthetically valuable spiro compounds from β-Naphthols under air is reported, in which N,N-dimethylaminoethanol (DMEA) serves as an efficient and unique C1 synthon. This transformation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…On the basis of these control experiments and previous literature reports, a reasonable mechanism of this transformation is proposed. As shown in Scheme , the mechanism initiates with the coordination of DMEA and Cu 2+ to form complex I , followed by the formation of radical cation II through a single-electron-transfer process.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…On the basis of these control experiments and previous literature reports, a reasonable mechanism of this transformation is proposed. As shown in Scheme , the mechanism initiates with the coordination of DMEA and Cu 2+ to form complex I , followed by the formation of radical cation II through a single-electron-transfer process.…”
Section: Resultssupporting
confidence: 57%
“…Recently, N , N -dimethylethanolamine (DMEA) was discovered to be a novel and versatile C1 synthon in our group . Compared with conventional C1 synthons such as DMF, DMSO, formaldehyde, and methanol, DMEA has shown some unique activities.…”
Section: Introductionmentioning
confidence: 99%
“…The examination of differen palladium salts showed that Pd(TFA)2 has higher catalytic activity than Pd(OAc)2 (entry 13), and the yield of 3a is raised to 89%. Whereafter, examination of different ligands (such as pyridine and phthalimide), previously proved in palladium-catalyzed aza-Wacke reactions [22][23][24][25], which not only failed to improve the reaction efficiency but it was also detrimental for this transformation (Entries 11, 12). Other Pd(II) catalysts, such as PdCl2 Pd(CH3CN)2Cl2, and Pd(PhCN)2Cl2, can not trigger the transformation, likely to be the difficulty in ligand exchange between the chloride ion and N-aryl phosphoramidates Finally, when the reaction was performed under an N2 atmosphere (Entry 14), 3a was isolated in only 7% of the yield, and the formation of palladium black indicated that O was used as an oxidant to regenerate the active palladium catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…3 To overcome this problem, chemists have creatively utilized reactive naphthols as substrates to build the spironaphthalenone backbones via intramolecular or intermolecular dearomatization. 4,5 While this elegant strategy is generally reliable, the preparation of the elaborately designed active naphthol substrates usually requires tedious synthetic steps and suffers from harsh reaction conditions. Thus, there is currently a strong impetus to develop more effective and sustainable protocols for the preparation of spironaphthalenone derivatives starting from easily obtainable substrates under mild conditions.…”
Section: Introductionmentioning
confidence: 99%